RESPON SISWA SD TERHADAP PEMBELAJARAN PENEMUAN BERBANTUAN ALAT PERAGA PADA MATERI VOLUM BALOK DAN KUBUS - Jayanti Putri Purwaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2016)
Teacher at SDN 4 Puyoh Kudus District rarely make the learning process through learning discoveries aided props on the material Volume beams and cubes. This is due, they are accustomed to using expository teaching methods which place more emphasis on the process of delivering the material verbally from teacher to student. Thus, the response of the students in the learning of the discovery needs to be examined. This study aims to investigate the response of primary school students towards learning mathematics through learning discoveries aided props. This research uses descriptive qualitative research design in which the subject of the study was nineteen students. Data collection techniques are by using questionnaires, observation sheets, documentation and interviews. The results showed that the students showed a positive response tehadap mathematics learning using discovery learning props aided by the average percentage of students who responded positively to 82.11%. In addition, the activity of students during the learning process using the learning-aided invention nice props with an average percentage of 83% of student activity. Keywords: Response of primary school students, learning discovery, Viewer Tool